Calreticulin Identified as One of the Androgen Response Genes That Trigger Full Regeneration of the Only Capable Mammalian Organ, the Deer Antler - Guo, Qianqian; Zheng, Junjun; Ba, Hengxing; Sun, Hongmei; Zhai, Jingjie; Wang, Wenying; Li, Chunyi (Frontiers in Cell and Developmental Biology, 2022)
Deer antlers are male secondary sexual characters that develop to become bone; they are unique appendages that, once lost, can fully regenerate from the permanent bony protuberances, or pedicles. Pedicle periosteum (PP) is the tissue that gives rise to the regenerating antlers with three differentiation stages, namely dormant (DoPP), potentiated (PoPP) and activated (AcPP). Thus far, the transition from the PoPP to the AcPP has not been studied. Our results showed that the AcPP cells maintained their original stem cell features by expressing mesenchymal stem cell (MSC) markers CD73, CD90 and CD105, although they had entered the proliferation mode. The differentially expressed genes (DEGs) in the AcPP compared with the PoPP were mainly involved in protein processing, cell cycle and calcium signaling pathways. Calreticulin (CALR), an androgen response gene, was significantly differentially up-regulated in the AcPP cells and its expression level was negatively regulated by androgens, in contrast to the currently known model systems where all regulation is positive. Down-regulation of CALR expression in the AcPP cells in vitro inhibited cell proliferation, induced apoptosis and inhibited cell cycle progression at the G1-S transition. Therefore, CALR is likely a down-stream mediator of androgen hormones for triggering initiation of antler regeneration. We believe that identification of CALR has not only discovered “one critical piece” of the “jigsaw puzzle” in the initiation of antler regeneration, but also helps in revealing the mechanism underlying this unique mammalian epimorphic regeneration and has also opened a new avenue for study of the nature of CALR regulation by androgen (putative binding partners), thus facilitating identification of potential molecule(s) for investigation as targets for clinical evaluation.